Complement Therapeutics - Lambris, John D.; Lambris, John D.; Holers, V. Michael.; Holers, V. Michael.; Ricklin, Daniel.; Ricklin, Daniel. (Advances in Experimental Medicine and Biology,, 2013)
This book highlights progress and trends in the rapidly evolving field of complement-related drug discovery and spotlights examples of clinical applications. As an integral part of innate immunity and critical mediator in homeostatic and inflammatory processes, the human complement system has been identified as contributor to a large number of disorders including ocular, cardiovascular, metabolic, autoimmune, and inflammatory diseases as well as in ischemia/reperfusion injury, cancer and sepsis. In addition, complement is often involved in adverse immune reactions to biomaterials, cell and organ transplants or drug delivery systems. Although the complement cascade with its close to 50 extracellular protein targets has long been recognized as an attractive system for therapeutic modulation, the past few years have seen a particularly strong boost in interest. Fueled by novel research insight and the marketing of the first complement-targeted drugs, a plethora of highly creative treatment approaches and potent drug candidates have recently emerged and are currently evaluated in disease models and clinical trials.   The chapters in this book cover a wide range of topics related to the development of complement therapeutics, ranging from the molecular and functional description of complement targets to the presentation of novel inhibitors, improved treatment strategies as well as examples of disease models and clinical applications. The broad and up-to-date overview on a highly versatile and dynamic field renders this book an indispensable source of information for researchers and clinicians dealing with therapeutic and disease-related aspects of the human complement system.